Leveraging regional immigration and immigration diversity for financing crowdfunding projects. Issue 1 (1st January 2021) - Di Pietro, Francesca
ABSTRACT: The study focuses on the role of regional immigration and immigration diversity in influencing entrepreneurs' ability to crowdfund their projects by leveraging the local crowd. Relying on an empirical analysis of 3250 individual investments via three Swiss reward-based crowdfunding platforms, it is found that higher immigration and immigration diversity levels in the region of the project proponent increase his/her ability to fulfil the funding needs by leveraging local backers (as opposed to backers from different regions). Immigration and immigration diversity constitute a cultural milieu that helps the financing of innovation and the development of the local entrepreneurial economy.